Influence of fibers on the mechanical properties and durability of ultra-high-performance concrete: A review. (15th July 2022) - Wen, Chengcheng; Zhang, Peng; Wang, Juan; Hu, Shaowei
Abstract: In recent years, ultra-high-performance concrete (UHPC) has attracted increasing interest owing to its superior mechanical properties and excellent durability. This paper introduces the enhancement mechanisms of various fibers on concrete materials and reviews the effects of volume fraction, shape, type, aspect ratio, and hybrid fiber combinations on the static and dynamic mechanical properties, fiber-matrix bonding behavior, and durability of UHPC. Furthermore, the empirical formulas and theoretical models for predicting the properties of UHPC are summarized. The results indicate that fibers have significant potential to enhance the tensile and fracture strengths of UHPC, and the optimal fiber volume fraction seems to be related to the fiber type. The aspect ratio has no noticeable effect on the properties of UHPC, whereas the effect of hybrid fiber combinations seems to be uncertain and depend on the synergistic effect of different types of fibers. Variations in the water/binder ratio, mix proportion, and curing system may also influence the results. In addition, the theoretical models and empirical formulas summarized in this paper can further enrich the design theory of UHPC and provide recommendations for future research. Highlights: Enhancement mechanisms of fibers on concrete materials are introduced. A variety of volume fraction, shape, type, aspect ratio, and hybrid fiber combinations are discussed. Effects of fibers on the mechanical properties and durability of UHPC are reviewed and compared with NSC and HSC. Empirical formulas and theoretical models for predicting UHPC performance are summarized. Further suggestions for the research and application of UHPC are proposed.